Development of a reproducible small intestinal microbiota model and its integration into the SHIME®-system, a dynamic in vitro gut model - Deyaert, Stef; Moens, Frédéric; Pirovano, Walter; van den Bogert, Bartholomeus; Klaassens, Eline Suzanne; Marzorati, Massimo; Van de Wiele, Tom; Kleerebezem, Michiel; Van den Abbeele, Pieter (Frontiers in Microbiology, 2023)
The human gastrointestinal tract consists of different regions, each characterized by a distinct physiology, anatomy, and microbial community. While the colonic microbiota has received a lot of attention in recent research projects, little is known about the small intestinal microbiota and its interactions with ingested compounds, primarily due to the inaccessibility of this region in vivo. This study therefore aimed to develop and validate a dynamic, long-term simulation of the ileal microbiota using the SHIME®-technology. Essential parameters were identified and optimized from a screening experiment testing different inoculation strategies, nutritional media, and environmental parameters over an 18-day period. Subjecting a synthetic bacterial consortium to the selected conditions resulted in a stable microbiota that was representative in terms of abundance (8.81  0.12 log(cells/mL)), composition and function. Indeed, the observed community mainly consisted of the genera Streptococcus, Veillonella, Enterococcus, Lactobacillus and Clostridium (qPCR and 16S rRNA gene targeted Illumina sequencing), while nutrient administration boosted lactate production followed by cross-feeding interactions towards acetate and propionate. Furthermore, similarly as in vivo, bile salts were only partially deconjugated and only marginally converted into secondary bile salts. After confirming reproducibility of the small intestinal microbiota model, it was integrated into the established M-SHIME® where it further increased the compositional relevance of the colonic community. This long-term in vitro model provides a representative simulation of the ileal bacterial community, facilitating research of the ileum microbiota dynamics and activity when, for example, supplemented with microbial or diet components. Furthermore, integration of this present in vitro simulation increases the biological relevance of the current M-SHIME® technology.